"All bets are off": Flexible engagement with music-listening technologies by autistic adults. (November 2021) - Matsuno, Michael; Auzenne, Deon; Chukoskie, Leanne
This qualitative study used semi-structured interviews to explore daily experiences with music among a convenience sample of 12 autistic adults interning at a video game development lab. Our analysis indicates that music technologies enabled autistic individuals to explore new music and to engage reflexively with personal taste and self-curation. We also show that participants used music to accompany a range of cognitive and emotional tasks. These findings are consistent with broader sociological literature on music-listening habits of typically developing adults and indicate that autistic adults use music to meet their personal needs. Our cohort also described expressly creative and proactive engagement with music, suggesting that habits with music may differ among unique sub-populations of autistic individuals.